Dimerization and lysine substitution of melittin have differing effects on bacteria - Matthyssen, Tamara; Li, Wenyi; Holden, James A.; Lenzo, Jason C.; Hadjigol, Sara; O’Brien-Simpson, Neil M. (Frontiers in Pharmacology, 2024)
Introduction Melittin is a potent antimicrobial peptide from bee venom that is effective against both Gram-positive and Gram-negative bacteria. However, it is extremely toxic to mammalian cells and, as yet, has no clinical use. Modifications to its amino acid sequence, cyclization, truncation, and dimerization have been attempted in order to reduce its toxicity whilst maintaining its antimicrobial activity. Methods In this study, we targeted the three lysine residues present in melittin and substituted them with lysine homologs containing shorter side chains (ornithine, Orn, diaminobutyric acid, Dab, and diaminopropanoic acid, Dap) and made both parallel and antiparallel melittin dimers to observe how lysine substitution and dimerization affects its activity and toxicity. The antibacterial activity of melittin and its analogs was tested against S. aureus (Gram-positive bacteria) and E. coli (Gram-negative bacteria), and cytotoxicity was tested against the mammalian cell lines HEK293 and H4IIE. Results Overall, dimerization and lysine substitution exhibited improved antimicrobial activity toward E. coli and limited improvement toward S. aureus. However, mammalian cell toxicity was only marginally reduced compared to native melittin. Interestingly, the parallel dimer was found to be marginally more active than the antiparallel dimer, indicating orientation maybe important for activity, although both dimers were less effective than the native and Lys-analog peptides toward S. aureus. Of the Lys substitutions, Dab and Dap improved melittin’s activity toward E. coli. Discussion Dimerization and Lys substitution of melittin improved the antimicrobial activity toward Gram-negative bacteria but did not significantly improve its activity toward Gram-positive bacteria. Some analogs also displayed reduced toxicity toward HEK293 and H4IIE cells but overall remained toxic at bactericidal concentrations. Our data indicates that although highly antibacterial, melittin’s toxicity is the major drawback in its potential use.